Dual‐polarized frequency selective absorber with in‐band reflection response. Issue 10 (1st July 2022) - Li, Zhihang; Zhang, Guanmao; Yang, Shuo; Lun, Yupeng; Che, Zonge; Yue, Juan; Suo, Junhong
Abstract: This paper proposes a frequency selective absorber with a notch reflection band. It consists of a lossy layer and a metal ground. The lossy layer is composed of the octagonal ring and meander‐line resonators connected in parallel on the same plane, which are used to obtain a wide absorption band and a notch reflection band, respectively. The simulation results show that there are two absorption bands from 2.22 to 6.8 GHz and 7.94 to 8.54 GHz, and there is a −3dB reflection band from 7.14 to 7.68 GHz. Moreover, the absorber also has the characteristics of compact structure, polarization‐independent, and angular stability. The equivalent circuit has been established and explained the performance of the proposed band‐notched absorber. The proposed band‐notched absorber is manufactured and measured, and the results are generally in good agreement with the full‐wave simulation results.